Critical role of potassium and sodium salts against insect-pest complex of rice - Chatterjee, Sitesh; Mallick, Rambilash; Gangopadhyay, Chirasree; Halder, Purnima; Dana, Indrani; Choudhury, Bijoy (ORYZA-An International Journal of Rice, 2021)
A field experiment was carried out at Rice Research Station, Chinsurah, Hooghly during rainy (kharif) season, 2016 and 2017 to evaluate the effects of potassium and sodium salts on whorl maggot, leaf folder and yellow stem borer of rice. The yield and yield attributing characters were observed and benefit cost ratio was calculated. The potassium salts viz. potassium chloride (KCl), potassium nitrate (KNO3), potassium sulfate (K2SO4), potassium dihydrogen phosphate (KH2PO4) and sodium salt as sodium chloride (NaCl) were applied by three modes viz. seed soaking for 12 hours before sowing, seedling root dipping for twelve hours before transplanting and foliar sprays at 30 and 50 days after transplanting (DAT). The experimental results revealed that the foliar spray with 1% potassium dihydrogen phosphate salt at 30 and 50 DAT was the best performer against rice insect-pests by lowering down the infestation of leaf folder, dead heart and white ear head and as well as responses for good yield. Maximum benefit was recorded with foliar spray of 1% sodium chloride salt.